Navigating uncertain waters: European public perceptions of integrated multi trophic aquaculture (IMTA). Issue 61 (July 2016) - Alexander, K.A.; Freeman, S.; Potts, T.
Highlights: European public more positive than negative about traditional aquaculture. Public awareness of IMTA universally low. Perceived potential benefits of IMTA include job creation and well-being. Region a key factor influencing perceptions of traditional aquaculture and IMTA. Abstract: Issues such as food safety, quality, health, animal welfare and the environment have become more important for seafood consumers and the general public in recent years, particularly in relation to aquaculture. Moving from monoculture to integrated multi-trophic aquaculture (IMTA), may remedy some of the concerns held by the public relating to these issues. Early studies from North America have found that consumers, and indeed the public in general, are supportive of more sustainable aquaculture production systems such as IMTA. The study described here adds to our understanding of the general public's perceptions of aquaculture in general and IMTA in particular, providing a European perspective. Furthermore, the study identifies factors which should be considered if advancing public recognition of IMTA. 2520 web-based survey questionnaires were compiled from across five countries (Ireland, Israel, Italy, Norway and the UK), aimed at investigating public understanding of aquaculture benefits and impacts, knowledge of IMTA, and also collecting demographic information. The data collected were analysed using descriptive statistics and logistic regression methods. This study determined that both positive and negative perceptions of aquaculture are held by the European general public and that they are influenced by a variety of geographic and demographic traits. The study also identified a lack of awareness of IMTA along with positive perceptions of the concept of integrated aquaculture, although the latter results should be treated with some caution. Based on the results, we conclude that there is clear scope to advance public awareness of the role of IMTA and this will be necessary to gain mainstream acceptance of this aquaculture practice.